Silica hydrogel contact lens and preparation method thereof
By modifying the combination of hyaluronic acid and acrylamide compounds, silicon hydrogel contact lenses with improved water retention and reduced hardness were prepared, which solved the problems of poor water retention and high hardness of existing silicon hydrogel contact lenses. Improves wear comfort and durability of lenses.
Patent Information
- Application Number
- CN202411578436.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-14
AI Technical Summary
Existing silicone hydrogel contact lenses have problems such as poor water retention, hard texture, and easy adsorption of proteins, which affects the comfort and safety of wearing.
Preliminary modification was performed by mixing hyaluronic acid with 2,3-epoxypropyl trimethylammonium chloride, and further modification was performed by adding glycidyl methacrylate, combining silicone monomers and acrylamide compounds. The polymerization reaction was carried out, and after ultraviolet curing and alkali solution soaking, silicon hydrogel contact lenses with improved water retention properties and reduced hardness were prepared.
It improves the hydrophilic and water-retaining properties of silicon hydrogel contact lenses, reduces the amount of protein adsorption, improves wear comfort and durability of lenses, and extends service life.
Smart Images

Figure BDA0005122448650000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicone gel materials, and in particular to a silicone hydrogel contact lens and a preparation method thereof. Background Art
[0002] Contact lenses are special lenses that can directly contact the cornea of the eyeball to achieve the effect of correcting vision or decorating the eyes. With the increasing number of myopic people, more and more people choose to wear contact lenses, which can correct vision without affecting normal activities. The contact lenses on the market are divided into ordinary hydrogel contact lenses and silicone hydrogel contact lenses. The oxygen permeability of ordinary hydrogel contact lenses depends on their water content. The higher the water content, the better the oxygen permeability, but this also means that the lens may absorb more tears and cause dry eyes; while the oxygen permeability of silicone hydrogel contact lenses far exceeds that of ordinary hydrogel lenses. As the main component of the material, silicon has a very high oxygen permeability, allowing oxygen to more easily penetrate the lens to reach the cornea. This high oxygen permeability helps reduce the risk of red eyes and corneal hypoxia, and is particularly suitable for long-term wear.
[0003] However, there are still many problems with existing silicone hydrogel contact lenses. First, because silicone hydrogel materials are relatively hard, and silicone hydrogel contact lenses are thicker than ordinary contact lenses, people with sensitive eyes or first-time wearers will have a strong foreign body sensation after wearing, which affects the comfort of wearing; secondly, due to the hardness of silicone hydrogel, if it is worn improperly, such as excessive force or unskilled operation, there is a risk of scratching the cornea; thirdly, silicone hydrogel contact lenses are usually more likely to adsorb lipid precipitation, so to a certain extent, it is not easy to clean. Thorough cleaning is required before and after each wearing to prevent residues from irritating the eyes or causing infection. If the cleaning is not thorough, these residues and bacteria may cause infection of the cornea and conjunctiva, leading to keratitis, conjunctivitis and other inflammations; finally, silicone hydrogel contact lenses have poor water retention, which leads to dry eyes, foreign body sensation and other problems during wearing. Therefore, in order to solve the above problems, technicians in this field are in urgent need of developing a silicone hydrogel contact lens with good water retention and soft texture. Summary of the invention
[0004] The purpose of the present invention is to provide a silicone hydrogel contact lens and a preparation method thereof, so as to solve the problems of poor water retention, hard texture and easy protein adsorption in existing silicone hydrogel contact lenses.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a silicone hydrogel contact lens, comprising the following steps:
[0007] 1) mixing hyaluronic acid with 2,3-epoxypropyltrimethylammonium chloride for preliminary modification, and then adding glycidyl methacrylate for further modification after the reaction to obtain modified hyaluronic acid;
[0008] 2) mixing siloxane monomer, 2-hydroxyethyl methacrylate, 1-vinyl-2-pyrrolidone, acrylamide compound, modified hyaluronic acid, a crosslinking agent, an initiator and a solvent to carry out polymerization reaction to obtain a prepolymer;
[0009] 3) defoaming the prepolymer and then injecting it into a contact lens mold and curing it under ultraviolet light to obtain a contact lens;
[0010] 4) The lens is sequentially immersed in an alkaline solution and then immersed in water to obtain a silicone hydrogel contact lens.
[0011] Preferably, the molar ratio of hyaluronic acid to 2,3-epoxypropyltrimethylammonium chloride in step 1) is 1:1 to 1.5;
[0012] The temperature of the preliminary modification is 45-60° C., and the time of the preliminary modification is 8-12 hours.
[0013] Preferably, the molar ratio of the methacrylic acid glyceride to the hyaluronic acid in step 1) is 1:1 to 1.5;
[0014] The temperature of the further modification is 50-70° C., and the time of the further modification is 5-12 hours.
[0015] Preferably, the mass ratio of the siloxane monomer, 2-hydroxyethyl methacrylate, 1-vinyl-2-pyrrolidone, acrylamide compound, modified hyaluronic acid, crosslinking agent, initiator and solvent in step 2) is 20-50:10-20:5-8:10-20:8-15:0.2-1:0.5-5:10-30.
[0016] Preferably, the siloxane monomer in step 2) includes one or more of 3,3,3-trifluoropropyltrimethoxysilane, trifluoropropyltriethoxysilane, γ-methacryloxypropyltri(trimethylsiloxy)silane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, 3-(acryloxy)propyltrimethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane;
[0017] The acrylamide compounds are acrylamide, methacrylamide, 1,4-butanediol dimethacrylate, and N,N'-methylenebisacrylamide.
[0018] Preferably, the cross-linking agent in step 2) includes one or more of ethylene glycol dimethacrylate, vinyl methacrylate and triethylene glycol di(meth)acrylate;
[0019] The initiator includes one or more of 2-hydroxy-2-methylpropiophenone, methyl benzoylformate, 2,2-dimethoxy-2-phenylacetophenone and 1-hydroxycycloethylphenylacetone.
[0020] Preferably, the polymerization reaction temperature in step 2) is 20-40° C., and the polymerization reaction time is 18-30 hours.
[0021] Preferably, the wavelength of the UV curing in step 3) is 315-400 nm, the time of UV curing is 30-180 min, and the temperature of UV curing is 60-90° C.
[0022] Preferably, the alkaline solution in step 4) is a potassium hydroxide solution or a sodium hydroxide solution;
[0023] The concentration of the alkaline solution is 0.1-0.5 mol / L.
[0024] The present invention also provides a silicone hydrogel contact lens prepared by the preparation method.
[0025] The present invention has at least the following beneficial effects:
[0026] The present invention adds modified hyaluronic acid and hydrophilic acrylamide compounds into the system when preparing silicone hydrogel contact lenses, which effectively improves the hydrophilic and water-retaining properties of silicone hydrogels; glycidyl acrylate is grafted onto hyaluronic acid and then introduced into silicone hydrogel contact lenses, which can reduce the hardness of hyaluronic acid and improve the comfort of the contact lenses; and by testing the protein adsorption amount of the contact lenses prepared by the present invention, it can be known that the silicone hydrogel contact lenses prepared by the present invention have a lower protein adsorption amount than commercially available silicone hydrogel contact lenses, which is beneficial to increasing the number of times the silicone hydrogel contact lenses are used. DETAILED DESCRIPTION
[0027] The present invention provides a method for preparing a silicone hydrogel contact lens, comprising the following steps:
[0028] 1) mixing hyaluronic acid with 2,3-epoxypropyltrimethylammonium chloride for preliminary modification, and then adding glycidyl methacrylate for further modification after the reaction to obtain modified hyaluronic acid;
[0029] 2) mixing siloxane monomer, 2-hydroxyethyl methacrylate, 1-vinyl-2-pyrrolidone, acrylamide compound, modified hyaluronic acid, a crosslinking agent, an initiator and a solvent to carry out polymerization reaction to obtain a prepolymer;
[0030] 3) defoaming the prepolymer and then injecting it into a contact lens mold and curing it under ultraviolet light to obtain a contact lens;
[0031] 4) The lens is sequentially immersed in an alkaline solution and then immersed in water to obtain a silicone hydrogel contact lens.
[0032] In the present invention, the molar ratio of hyaluronic acid to 2,3-epoxypropyltrimethylammonium chloride in step 1) is 1:1 to 1.5;
[0033] In the present invention, the temperature of the preliminary modification is 45-60°C, preferably 48-58°C, more preferably 50-55°C, more preferably 52-55°C; the time of the preliminary modification is 8-12h, preferably 8.5-11.5h, more preferably 9-11h, more preferably 10h.
[0034] In the present invention, the molar ratio of the methacrylic acid glyceride to the hyaluronic acid in step 1) is 1:1-1.5, preferably 1:1.1-1.4, and more preferably 1:1.2-1.3.
[0035] In the present invention, the temperature for further modification is 50-70°C, preferably 55-65°C, more preferably 58-63°C, and more preferably 60°C; the time for further modification is 5-12h, preferably 6-11h, more preferably 7-10h, and more preferably 8-9h.
[0036] In the present invention, the mass ratio of the siloxane monomer, 2-hydroxyethyl methacrylate, 1-vinyl-2-pyrrolidone, acrylamide compound, modified hyaluronic acid, crosslinking agent, initiator and solvent in step 2) is 20-50:10-20:5-8:10-20:8-15:0.2-1:0.5-5:10-30, preferably 25-45:12-18:5.5 ~7.5:12~18:9~14:0.4~1.5:1~4:13~28, more preferably 30~40:14~16:6~7:13~16:10~13:0.6~1.2:2.5~3.5:15~25, more preferably 35~38:15:6~6.5:14~15:11~12:0.8~1:2.8~3.2:18~22.
[0037] In the present invention, the siloxane monomer described in step 2) includes one or more of 3,3,3-trifluoropropyltrimethoxysilane, trifluoropropyltriethoxysilane, γ-methacryloxypropyltri(trimethylsiloxy)silane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, 3-(acryloxy)propyltrimethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0038] In the present invention, the acrylamide compound is acrylamide, methacrylamide, 1,4-butanediol dimethacrylate, and N,N'-methylenebisacrylamide.
[0039] In the present invention, the cross-linking agent in step 2) includes one or more of ethylene glycol dimethacrylate, vinyl methacrylate and triethylene glycol di(meth)acrylate.
[0040] In the present invention, the initiator includes one or more of 2-hydroxy-2-methylpropiophenone, methyl benzoylformate, 2,2-dimethoxy-2-phenylacetophenone and 1-hydroxycycloethylphenylpropiophenone.
[0041] In the present invention, the solvent in step 2) includes one or more of ethanol, propanol, ethylene glycol, n-butanol and acetone.
[0042] In the present invention, the temperature of the polymerization reaction in step 2) is 20-40°C, preferably 22-38°C, further preferably 25-35°C, and more preferably 28-32°C; the time of the polymerization reaction is 18-30h, preferably 20-28h, further preferably 22-26h, and more preferably 23-25h.
[0043] In the present invention, the polymerization reaction in step 2) needs to be carried out under light-proof conditions.
[0044] In the present invention, the wavelength of the UV curing in step 3) is 315-400 nm, which can be optionally 320 nm, 330 nm, 340 nm, 350 nm, 365 nm, 380 nm or 395 nm; the UV curing time is 30-180 min, preferably 45-150 min, and more preferably 60-120 min; the UV curing temperature is 60-90° C., preferably 65-85° C., and more preferably 70-80° C.
[0045] In the present invention, the alkaline solution in step 3) is a potassium hydroxide solution or a sodium hydroxide solution.
[0046] In the present invention, the concentration of the alkaline solution is 0.1 to 0.5 mol / L, preferably 0.2 to 0.4 mol / L, and more preferably 0.3 mol / L.
[0047] In the present invention, the soaking time of the alkaline solution in step 4) is 20 to 60 minutes, preferably 25 to 50 minutes, and more preferably 30 to 40 minutes.
[0048] In the present invention, the water immersion treatment time in step 4) is 24 to 48 hours, preferably 28 to 44 hours, more preferably 32 to 40 hours, and more preferably 36 to 38 hours.
[0049] In the present invention, the purpose of soaking the lens with alkaline solution and water in step 4) is to remove the residual monomers in the silicone hydrogel contact lens and fully hydrate the silicone hydrogel contact lens.
[0050] The present invention also provides a silicone hydrogel contact lens prepared by the preparation method.
[0051] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0052] Example 1
[0053] 1 mol of hyaluronic acid was mixed with 1.2 mol of 2,3-epoxypropyltrimethylammonium chloride, and heated to 45°C in a water bath for preliminary modification. After 10 hours, 1.2 mol of glycidyl methacrylate was added to the mixed system, and the reaction was continued at 60°C with stirring for 7 hours for further modification. After the modification was completed, 0.5 g of sodium hydroxide was added to the system and stirred evenly. Then 30 mL of anhydrous ethanol was added to the system, filtered, and the precipitate was washed 3 times with anhydrous ethanol. Finally, 0.1 mol / L of hydrochloric acid solution was added to the precipitate, and the pH value of the system was adjusted to 6 to obtain modified hyaluronic acid.
[0054] 4 g of 3,3,3-trifluoropropyltrimethoxysilane, 2 g of 2-hydroxyethyl methacrylate, 1.2 g of 1-vinyl-2-pyrrolidone, 2 g of acrylamide, 1.5 g of modified hyaluronic acid, 0.2 g of vinyl methacrylate, 0.1 g of methyl benzoylformate and 2 mL of propanol were mixed, and polymerization was carried out at 25° C. in the dark to obtain a prepolymer after the reaction for 20 hours. The prepolymer was shaken and defoamed (20° C. in the dark) and then injected into a contact lens mold, and then cured under ultraviolet light at 60° C. and 365° C. for 30 minutes.
[0055] After the cured lens and the mold are soaked in ultrapure water for 2 hours, the lens is peeled off and soaked in a 0.1 mol / L potassium hydroxide solution for 40 minutes. After the lens is taken out, it is rinsed with ultrapure water for 3 times and then soaked in ultrapure water for 48 hours to fully hydrate, thereby obtaining a silicone hydrogel contact lens.
[0056] Example 2
[0057] 1 mol of hyaluronic acid was mixed with 1.5 mol of 2,3-epoxypropyltrimethylammonium chloride, and heated to 60°C in a water bath for preliminary modification. After 8 hours, 1.3 mol of glycidyl methacrylate was added to the mixed system, and the reaction was continued at 50°C with stirring for 10 hours for further modification. After the modification was completed, 0.8 g of sodium hydroxide was added to the system and stirred evenly. Then, 50 mL of anhydrous ethanol was added to the system, filtered, and the precipitate was washed 3 times with anhydrous ethanol. Finally, 0.1 mol / L of hydrochloric acid solution was added to the precipitate, and the pH value of the system was adjusted to 5.8 to obtain modified hyaluronic acid.
[0058] 7 g of γ-methacryloxypropyl tri(trimethylsiloxy)silane, 3 g of 2-hydroxyethyl methacrylate, 1.3 g of 1-vinyl-2-pyrrolidone, 3 g of 1,4-butanediol dimethacrylate, 2 g of modified hyaluronic acid, 0.2 g of triethylene glycol di(meth)acrylate, 0.6 g of 1-hydroxycycloethylphenylacetone and 1.5 mL of ethylene glycol were mixed, and polymerization reaction was carried out at 20° C. in the dark to obtain a prepolymer after the reaction for 18 hours; the prepolymer was shaken and defoamed (20° C. in the dark) and then injected into a contact lens mold, and then cured at 70° C. and 395 nm ultraviolet light for 60 minutes.
[0059] After the cured lens and the mold are soaked in ultrapure water for 2.5 hours, the lens is peeled off and soaked in a 0.5 mol / L sodium hydroxide solution for 30 minutes. After the lens is taken out, it is rinsed with ultrapure water for 3 times and then soaked in ultrapure water for 48 hours to fully hydrate, thereby obtaining a silicone hydrogel contact lens.
[0060] Example 3
[0061] 1 mol of hyaluronic acid was mixed with 1.3 mol of 2,3-epoxypropyltrimethylammonium chloride, and heated to 60°C in a water bath for preliminary modification. After 8 hours, 1.3 mol of glycidyl methacrylate was added to the mixed system, and the reaction was continued at 60°C with stirring for 12 hours for further modification. After the modification was completed, 0.5 g of potassium hydroxide was added to the system and stirred evenly. Then 30 mL of anhydrous ethanol was added to the system, filtered, and the precipitate was washed 3 times with anhydrous ethanol. Finally, 0.1 mol / L of hydrochloric acid solution was added to the precipitate, and the pH value of the system was adjusted to 6.2 to obtain modified hyaluronic acid.
[0062] 4 g of γ-methacryloxypropyltrimethoxysilane, 2 g of 2-hydroxyethyl methacrylate, 1.2 g of 1-vinyl-2-pyrrolidone, 2 g of N,N'-methylenebisacrylamide, 1.5 g of modified hyaluronic acid, 0.2 g of vinyl methacrylate, 0.1 g of methyl benzoylformate and 2 mL of acetone were mixed, and polymerization was carried out at 40° C. in the dark to obtain a prepolymer after the reaction for 20 hours. The prepolymer was shaken and defoamed (20° C. in the dark) and then injected into a contact lens mold, and then cured at 80° C. and 350 nm ultraviolet light for 120 minutes.
[0063] After the cured lens and the mold are soaked in ultrapure water for 3 hours, the lens is peeled off and soaked in a 0.3 mol / L potassium hydroxide solution for 30 minutes. After the lens is taken out, it is rinsed with ultrapure water for 4 times and then soaked in ultrapure water for 48 hours to fully hydrate, thereby obtaining a silicone hydrogel contact lens.
[0064] Example 4
[0065] 2 mol of hyaluronic acid was mixed with 2.5 mol of 2,3-epoxypropyltrimethylammonium chloride, and heated to 55°C in a water bath for preliminary modification. After 11 hours, 2.5 mol of glycidyl methacrylate was added to the mixed system, and the reaction was continued at 70°C with stirring for 5 hours for further modification. After the modification was completed, 0.8 g of sodium hydroxide was added to the system and stirred evenly. Then, 50 mL of anhydrous ethanol was added to the system, filtered, and the precipitate was washed 4 times with anhydrous ethanol. Finally, 0.1 mol / L of hydrochloric acid solution was added to the precipitate, and the pH value of the system was adjusted to 5.6 to obtain modified hyaluronic acid.
[0066] 5 g of 3-(acryloyloxy)propyltrimethoxysilane, 4 g of 2-hydroxyethyl methacrylate, 1.5 g of 1-vinyl-2-pyrrolidone, 5 g of 1,4-butanediol dimethacrylate, 3 g of modified hyaluronic acid, 0.3 g of ethylene glycol dimethacrylate, 1 g of 2,2-dimethoxy-2-phenylacetophenone and 2.5 mL of n-butanol were mixed, and polymerization was carried out at 30° C. in the dark to obtain a prepolymer after the reaction for 26 hours. The prepolymer was shaken and defoamed (20° C. in the dark) and then injected into a contact lens mold, and then cured at 65° C. and 365 nm ultraviolet light for 60 minutes.
[0067] After the cured lens and the mold are soaked in ultrapure water for 2 hours, the lens is peeled off and soaked in a 0.1 mol / L sodium hydroxide solution for 20 minutes. After the lens is taken out, it is rinsed with ultrapure water for 3 times and then soaked in ultrapure water for 36 hours to fully hydrate, thereby obtaining a silicone hydrogel contact lens.
[0068] Example 5
[0069] 2 mol of hyaluronic acid was mixed with 3 mol of 2,3-epoxypropyltrimethylammonium chloride, and heated to 58°C in a water bath for preliminary modification. After 12 hours, 3 mol of glycidyl methacrylate was added to the mixed system, and the reaction was continued at 65°C with stirring for 7 hours for further modification. After the modification was completed, 1.2 g of potassium hydroxide was added to the system and stirred evenly. Then, 50 mL of anhydrous ethanol was added to the system, filtered, and the precipitate was washed 5 times with anhydrous ethanol. Finally, 0.1 mol / L of hydrochloric acid solution was added to the precipitate, and the pH value of the system was adjusted to 5.7 to obtain modified hyaluronic acid.
[0070] 5 g of trifluoropropyltriethoxysilane, 1.6 g of 2-hydroxyethyl methacrylate, 0.8 g of 1-vinyl-2-pyrrolidone, 1.8 g of methacrylamide, 2 g of modified hyaluronic acid, 0.1 g of triethylene glycol di(meth)acrylate, 0.5 g of 1-hydroxycycloethylphenylacetone and 2 mL of ethylene glycol were mixed, and polymerization was carried out at 32° C. in the dark to obtain a prepolymer after the reaction for 28 hours; the prepolymer was shaken and defoamed (20° C. in the dark) and then injected into a contact lens mold, and then cured under 380 nm ultraviolet light for 150 minutes.
[0071] After the cured lens and the mold are soaked in ultrapure water for 2 hours, the lens is peeled off and soaked in a 0.2 mol / L potassium hydroxide solution for 50 minutes. After the lens is taken out, it is rinsed with ultrapure water for 5 times and then soaked in ultrapure water for 38 hours to fully hydrate, thereby obtaining a silicone hydrogel contact lens.
[0072] Comparative Example 1
[0073] The only difference between this comparative example and Example 1 is that unmodified hyaluronic acid is used to prepare the silicone hydrogel contact lens.
[0074] 4 g of 3,3,3-trifluoropropyltrimethoxysilane, 2 g of 2-hydroxyethyl methacrylate, 1.2 g of 1-vinyl-2-pyrrolidone, 2 g of acrylamide, 1.5 g of hyaluronic acid, 0.2 g of vinyl methacrylate, 0.1 g of methyl benzoylformate and 2 mL of propanol were mixed, and polymerization was carried out at 25° C. in the dark to obtain a prepolymer after the reaction for 20 hours. The prepolymer was shaken and defoamed (20° C. in the dark) and then injected into a contact lens mold, and then cured under ultraviolet light at 60° C. and 365° C. for 30 minutes.
[0075] After the cured lens and the mold are soaked in ultrapure water for 2 hours, the lens is peeled off and soaked in a 0.1 mol / L potassium hydroxide solution for 40 minutes. After the lens is taken out, it is rinsed with ultrapure water for 3 times and then soaked in ultrapure water for 48 hours to fully hydrate, thereby obtaining a silicone hydrogel contact lens.
[0076] Comparative Example 2
[0077] The only difference between this comparative example and Example 1 is that no modified hyaluronic acid is added during the preparation of the silicone hydrogel contact lens.
[0078] 4 g of 3,3,3-trifluoropropyltrimethoxysilane, 2 g of 2-hydroxyethyl methacrylate, 1.2 g of 1-vinyl-2-pyrrolidone, 2 g of acrylamide, 0.2 g of vinyl methacrylate, 0.1 g of methyl benzoylformate and 2 mL of propanol were mixed, and polymerization was carried out at 25° C. in the dark to obtain a prepolymer after 20 h of reaction. The prepolymer was shaken for defoaming (20° C. in the dark) and then injected into a contact lens mold, and then cured under ultraviolet light at 60° C. and 365° C. for 30 min.
[0079] After the cured lens and the mold are soaked in ultrapure water for 2 hours, the lens is peeled off and soaked in a 0.1 mol / L potassium hydroxide solution for 40 minutes. After the lens is taken out, it is rinsed with ultrapure water for 3 times and then soaked in ultrapure water for 48 hours to fully hydrate, thereby obtaining a silicone hydrogel contact lens.
[0080] Comparative Example 3
[0081] The only difference between this comparative example and Example 1 is that 2-hydroxyethyl methacrylate and 1-vinyl-2-pyrrolidone are not added during the preparation of the silicone hydrogel contact lens.
[0082] 1 mol of hyaluronic acid was mixed with 1.2 mol of 2,3-epoxypropyltrimethylammonium chloride, and heated to 45°C in a water bath for preliminary modification. After 10 hours, 1.2 mol of glycidyl methacrylate was added to the mixed system, and the reaction was continued at 60°C with stirring for 7 hours for further modification. After the modification was completed, 0.5 g of sodium hydroxide was added to the system and stirred evenly. Then 30 mL of anhydrous ethanol was added to the system, filtered, and the precipitate was washed 3 times with anhydrous ethanol. Finally, 0.1 mol / L of hydrochloric acid solution was added to the precipitate, and the pH value of the system was adjusted to 6 to obtain modified hyaluronic acid.
[0083] 4 g of 3,3,3-trifluoropropyltrimethoxysilane, 2 g of acrylamide, 1.5 g of modified hyaluronic acid, 0.2 g of vinyl methacrylate, 0.1 g of methyl benzoylformate and 2 mL of propanol were mixed, and polymerization was carried out at 25°C in the dark to obtain a prepolymer after 20 h of reaction. The prepolymer was injected into a contact lens mold after shaking and defoaming (20°C, in the dark), and then cured under ultraviolet light at 60°C and 365 for 30 min.
[0084] After the cured lens and the mold are soaked in ultrapure water for 2 hours, the lens is peeled off and soaked in a 0.1 mol / L potassium hydroxide solution for 40 minutes. After the lens is taken out, it is rinsed with ultrapure water for 3 times and then soaked in ultrapure water for 48 hours to fully hydrate, thereby obtaining a silicone hydrogel contact lens.
[0085] The oxygen permeability coefficient, water retention capacity, protein adsorption performance and monomer leaching rate of the silicone hydrogel contact lenses prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were tested. The test results are shown in Table 1.
[0086] The specific test method is as follows:
[0087] 1. Use OX2 / 230 oxygen permeability test system to test the oxygen permeability coefficient of silicone hydrogel contact lenses:
[0088] 99.9% oxygen is used as the test gas and 2% hydrogen-containing nitrogen is used as the carrier gas; the lens sample is placed on the smooth annular surface of the test chamber coated with vacuum grease to ensure that the sample has no wrinkles. The upper part of the test chamber is buckled onto the lower part of the test chamber containing the sample, clamped, and a certain amount of distilled water is injected into the surrounding groove. The test chamber cover is closed, and the carrier gas is set to flow into the upper and lower parts of the test chamber at a rate of 50mL / min. After 3 minutes, the flow rate drops to 10mL / min and is maintained for 30 minutes. At this time, the residual oxygen in the test chamber is continuously released from the lens sample, and the carrier gas carrying oxygen is transported to the coulomb sensor. The output of the sensor will first rise rapidly to a peak value, and then gradually stabilize at a lower value until the voltage stabilizes at a lower value, which is recorded as V0. Subsequently, oxygen and carrier gas are maintained at the final rate of deoxygenation (10mL / min) to flow into the upper and lower sides of the test chamber respectively. Oxygen passes through the lens sample and enters the coulomb sensor to output voltage. When the output value stabilizes to a value, the voltage value at this time is the final value, which is recorded as V E , according to q(O2)=K×(V E -V0) / RL to calculate the oxygen flow rate (μLO2 / s), where K is the calibration constant, V E is the final voltage output, V0 is the zero voltage output, and RL is the load impedance; then the oxygen permeability coefficient of the lens is calculated according to Dk=t×q(O2)×0.001 / (PA×A), where Dk is the oxygen permeability coefficient of the test sample, in units of 10 -11 (cm 2 / s)·[mLO2 / (mL·hPa)]; PA is (atmospheric pressure-water vapor pressure), in hPa; t is radial thickness or average harmonic center thickness, in cm; A is the exposed area of the test sample, in cm 2 ; 0.001 is the coefficient for converting μL to mL.
[0089] First, the standard material SRM1470, whose Dk / t is 0.072±0.0045Dk / t, is tested, and then the oxygen flow rate q(O2) and the normal constant K are derived using the above formula.
[0090] 2. After the silicone hydrogel contact lens is dried, test its surface contact angle.
[0091] 3. The silicone hydrogel contact lenses prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were placed in a watch glass, 500 μmL of distilled water was added, and the weight change was measured after placing in a ventilated and dry place for 3 minutes. The ambient temperature was 28° C. to test the water retention capacity.
[0092] 4. Prepare a lactoferrin solution (Lactoferrin Chemical Structure CAS No.: 936541-36-5) with a concentration of 8 mg / mL to simulate the protein concentration in tears. Soak the silicone hydrogel contact lenses in 5 mL of the above lactoferrin solution and seal the container to prevent the solution from evaporating. Take samples after soaking for 4 h and 8 h to detect the concentration of lactoferrin in the solution.
[0093] 5. Test the monomer leaching rate of silicone hydrogel contact lenses according to the national standard "GBT 11417.7-2012 Ophthalmic Optics Contact Lenses Part 7: Test Methods for Physical and Chemical Properties".
[0094] Table 1 Performance test results of silicone hydrogel contact lenses prepared in Examples 1 to 5 and Comparative Examples 1 to 3
[0095]
[0096]
[0097] According to the test data in Table 1, the silicone hydrogel contact lens prepared by modifying hyaluronic acid with 2,3-epoxypropyltrimethylammonium chloride and glycidyl methacrylate and then with other raw materials in the embodiment of the present invention has better water retention and hydrophilicity than Comparative Example 1 and Comparative Example 2, and has a smaller contact angle with water and a lower amount of water evaporation within 3 minutes; Comparative Example 1 only adds unmodified hyaluronic acid when preparing silicone hydrogel contact lenses, and although the hydrophilicity and water retention are improved compared with the silicone hydrogel contact lenses without hyaluronic acid added in Comparative Example 2, the improvement effect is limited. In addition, the present invention adds 2-hydroxyethyl methacrylate and 1-vinyl-2-pyrrolidone during the preparation process, which improves the problem that the silicone hydrogel contact lenses adsorb more protein and affect wearing, while Comparative Example 3 does not add 2-hydroxyethyl methacrylate and 1-vinyl-2-pyrrolidone during the preparation process, and has a higher protein adsorption amount and adsorption rate in the lactoferrin solution, which is not conducive to long-term wearing.
[0098] The silicone hydrogel contact lens prepared in the embodiment of the present invention has better hydrophilic and water-retaining properties, and reduces the protein adsorption performance of the silicone hydrogel contact lens, which can improve the comfort during wearing and the durability of the lens, and is conducive to extending the service life of the silicone hydrogel contact lens.
[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a silicone hydrogel contact lens, characterized in that: The following steps are involved: 1) mixing hyaluronic acid with 2,3-epoxypropyltrimethylammonium chloride for preliminary modification, and then adding glycidyl methacrylate for further modification after the reaction to obtain modified hyaluronic acid; 2) mixing siloxane monomer, 2-hydroxyethyl methacrylate, 1-vinyl-2-pyrrolidone, acrylamide compound, modified hyaluronic acid, a crosslinking agent, an initiator and a solvent to carry out polymerization reaction to obtain a prepolymer; 3) defoaming the prepolymer and then injecting it into a contact lens mold and curing it under ultraviolet light to obtain a contact lens; 4) The lens is sequentially immersed in an alkaline solution and then immersed in water to obtain a silicone hydrogel contact lens.
2. The method for preparing a silicone hydrogel contact lens according to claim 1, characterized in that: The molar ratio of hyaluronic acid to 2,3-epoxypropyltrimethylammonium chloride in step 1) is 1:1 to 1.5; The temperature of the preliminary modification is 45-60° C., and the time of the preliminary modification is 8-12 hours.
3. The method for preparing a silicone hydrogel contact lens according to claim 2, characterized in that: The molar ratio of the methacrylic acid glyceride to the hyaluronic acid in step 1) is 1:1 to 1.5; The temperature of the further modification is 50-70° C., and the time of the further modification is 5-12 hours.
4. The method for preparing a silicone hydrogel contact lens according to claim 2 or 3, characterized in that: The mass ratio of the siloxane monomer, 2-hydroxyethyl methacrylate, 1-vinyl-2-pyrrolidone, acrylamide compound, modified hyaluronic acid, crosslinking agent, initiator and solvent described in step 2) is 20-50:10-20:5-8:10-20:8-15:0.2-1:0.5-5:10-30.
5. The method for preparing a silicone hydrogel contact lens according to claim 4, characterized in that: The siloxane monomer described in step 2) includes one or more of 3,3,3-trifluoropropyltrimethoxysilane, trifluoropropyltriethoxysilane, γ-methacryloxypropyltri(trimethylsiloxy)silane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, 3-(acryloxy)propyltrimethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane; The acrylamide compounds are acrylamide, methacrylamide, 1,4-butanediol dimethacrylate, and N,N'-methylenebisacrylamide.
6. The method for preparing a silicone hydrogel contact lens according to claim 5, characterized in that: The crosslinking agent in step 2) includes one or more of ethylene glycol dimethacrylate, vinyl methacrylate and triethylene glycol di(meth)acrylate; The initiator includes one or more of 2-hydroxy-2-methylpropiophenone, methyl benzoylformate, 2,2-dimethoxy-2-phenylacetophenone and 1-hydroxycycloethylphenylacetone.
7. The method for preparing a silicone hydrogel contact lens according to claim 6, characterized in that: The polymerization reaction temperature in step 2) is 20-40° C., and the polymerization reaction time is 18-30 hours.
8. The method for preparing a silicone hydrogel contact lens according to any one of claims 5 to 7, characterized in that: The wavelength of the ultraviolet light curing in step 3) is 315-400 nm, the time of the ultraviolet light curing is 30-180 min, and the temperature of the ultraviolet light curing is 60-90° C.
9. The method for preparing a silicone hydrogel contact lens according to claim 8, characterized in that: The alkaline solution in step 4) is a potassium hydroxide solution or a sodium hydroxide solution; The concentration of the alkaline solution is 0.1-0.5 mol / L.
10. The silicone hydrogel contact lens prepared by the method for preparing a silicone hydrogel contact lens according to any one of claims 1 to 9.
Citation Information
Cited By
High-oxygen-permeability silicone hydrogel contact lens material and preparation method thereof
CN120623408A
Method and system for preparation of myopia prevention and control soft hydrophilic contact lens with defocus and contrast cooperative regulation
CN122788301A